Frecuencia de infección por helicobacter pylori, determinado mediante el método inmunocromatográfico en heces para la detección de antígenos de h. Pylori, en niños/as de 7 – 10 años de la escuela fiscal vespertina “José Ángel Palacio”, en comparación con los niños/as de la escuela particular matutina “Corporación Educativa S.E.I. - Zúñiga Román, Ivanova del Cisne (2010)
Helicobacter pylori is a small, spiral-shaped bacterium that lives in the surface of the stomach and duodenum. It is implicated in the etiology of a variety of gastrointestinal diseases, including duodenal and gastric ulcer, non-ulcer dyspepsia and active and chronic gastritis. The infection by Helicobacter pylori is one of the most frequently in the human being and it’s calculate about 40% to 50% of the population around the world is affected. In developed countries, like UU.EE, the annual incidence of infection by H. pylori it is about 0.5% and 1% to youngers of 10 years. By the way, it is estimated in developing countries, the majority of people (about 80%) is infected with H. pylori in an average age of 10 years. It has investigated a lot of factors, but all of them have as common factor the economic low level, the stacking, housing in bad conditions, contaminated water and the blood relationship. The present investigation, called: “Infection frecuency by Helicobacter pylori, determinate using the chromatographic immunoassay method in feces for the detection of antigens of H. pylori, in children of 7-10 years of the “José Ángel Palacio” school in comparison with children of the “Corporation Educative S.E.I” school, it shows us that the major frequency of infection by Helicobacter pylori in children of “José Ángel Palacio” school with the 54%, have a life style features by the shortage of drinkable water, stacking, to live together with animals, to have habits bad of hygiene, the economic low level, etc; in comparison with children of “Corporation Educative S.E.I” school with the 26%, they have with all the basis services such us: drinkable water, comfortable infrastructure, not live together with animals, to have good habits of hygiene, a economic high level, and others.